The war report : armed conflict in 2013 - Casey-Maslen, Stuart (Oxford University Press, 2014)
OF APPLICABLE INTERNATIONAL LAWHISTORY OF THE CONFLICT; PARTIES TO THE CONFLICT; CASUALTIES; WAR CRIMES ALLEGATIONS, INVESTIGATIONS, AND PROSECUTIONS; Military occupation of Cyprus by Turkey in 2013; CLASSIFICATION OF THE CONFLICT; SUMMARY OF APPLICABLE INTERNATIONAL LAW; HISTORY OF THE CONFLICT; PARTIES TO THE CONFLICT; CASUALTIES; WAR CRIMES ALLEGATIONS, INVESTIGATIONS, AND PROSECUTIONS; Military occupation of Eritrea by Ethiopia in 2013; CLASSIFICATION OF THE CONFLICT; SUMMARY OF APPLICABLE INTERNATIONAL LAW; HISTORY OF THE CONFLICT; PARTIES TO THE CONFLICT; CASUALTIES.